2022
DOI: 10.1093/mnras/stac371
|View full text |Cite
|
Sign up to set email alerts
|

ExoMol line lists – XLV. Rovibronic molecular line lists of calcium monohydride (CaH) and magnesium monohydride (MgH)

Abstract: New molecular line lists for calcium monohydride (40Ca1H) and magnesium monohydride (24Mg1H) and its minor isotopologues (25Mg1H and 26Mg1H) are presented. The rotation-vibration-electronic (rovibronic) line lists, named XAB, consider transitions involving the X 2Σ+, A 2Π, and B/B′ 2Σ+ electronic states in the 0–30 000 cm−1 region (wavelengths λ > 0.33 μm) and are suitable for temperatures up to 5000 K. A comprehensive analysis of the published spectroscopic literature on CaH and MgH is used to obtain n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Such a refinement allows for a subset of the energies to be provided with very high accuracy, as has been demonstrated in similar projects (Bowesman et al 2022). This allows for high-accuracy transition frequency predictions to be made (Al-Derzi et al 2021), making the final line list well suited for high-resolution studies (Bowesman et al 2021;Owens et al 2022).…”
Section: Methodsmentioning
confidence: 93%
“…Such a refinement allows for a subset of the energies to be provided with very high accuracy, as has been demonstrated in similar projects (Bowesman et al 2022). This allows for high-accuracy transition frequency predictions to be made (Al-Derzi et al 2021), making the final line list well suited for high-resolution studies (Bowesman et al 2021;Owens et al 2022).…”
Section: Methodsmentioning
confidence: 93%
“…This is a rather realistic case, as the input spectral constants to PGOPHER listed in Table 3 were determined by the observed transitions. 46 As for the input to Duo , the potential energy curve was shifted from an empirically determined one 47 , 48 to reproduce the B 0 constant given in Table 3 , that is; The curves of spin-rotation and hyperfine couplings were defined as Note that the contribution of D 0 is not allowed for when only one contracted basis function is used in Duo . Just like the B v constant, Duo does not use rotational constants, D v , H v , etc., either, and introduction of these centrifugal distortion would require manipulation of the potential energy curves which are beyond the scope of this work.…”
Section: Numerical Verificationmentioning
confidence: 99%
“…This is a rather realistic case, as the input spectral constants to PGOPHER listed in Table 3 were determined by the observed transitions. 46 As for the input to DUO, the potential energy curve was shifted from an empirically determined one 47,48 to reproduce the B 0 constant given in Table 3, that is;…”
Section: Numerical Verificationmentioning
confidence: 99%
“…As we have neglected the B 2 Σ + state and its associated couplings in our spectroscopic model, there will no doubt be an impact on the accuracy that could be achieved had we been able to incorporate them. Even adding a "dummy" coupling curve as a free fitted parameter can improve the accuracy of the spectroscopic model as is commonly seen for diatomics studied by the ExoMol project, for example, see CaH (Owens et al 2022). The à 2 Π state is expected to acquire a significant fraction of B 2 Σ + character through the vibronic interaction (Coxon et al 1994) and recently it was shown that the inclusion of the B-à couplings can improve the calculation of vibronic branching ratios in CaOH (Zhang et al 2021), which are needed when designing efficient laser-cooling schemes.…”
Section: Refinement Of the ã 2 π Potential Energy Surfacementioning
confidence: 99%